Marking the hours: English people and their prayers, 1240 - 1570 - Duffy, Eamon (Yale University Press, 2006)
"In this richly illustrated book, religious historian Eamon Duffy discusses the Book of Hours, unquestionably the most intimate and most widely used book of the later Middle Ages. He examines surviving copies of the personal prayer books which were used for private, domestic devotions, and in which people commonly left traces of their lives. Manuscript prayers, biographical jottings, affectionate messages, autographs, and pious paste-ins often crowd the margins, flyleaves, and blank spaces of such books. From these sometimes clumsy jottings, viewed by generations of librarians and art historians as blemishes at best, vandalism at worst, Duffy teases out precious clues to the private thoughts and public contexts of their owners, and insights into the times in which they lived and prayed. His analysis has a special relevance for the history of women, since women feature very prominently among the identifiable owners and users of the medieval Book of Hours."--From source other than the Library of Congress